2012
DOI: 10.1093/bioinformatics/bts180
|View full text |Cite
|
Sign up to set email alerts
|

optiCall: a robust genotype-calling algorithm for rare, low-frequency and common variants

Abstract: Motivation: Existing microarray genotype-calling algorithms adopt either SNP-by-SNP (SNP-wise) or sample-by-sample (sample-wise) approaches to calling. We have developed a novel genotype-calling algorithm for the Illumina platform, optiCall, that uses both SNP-wise and sample-wise calling to more accurately ascertain genotypes at rare, low-frequency and common variants.Results: Using data from 4537 individuals from the 1958 British Birth Cohort genotyped on the Immunochip, we estimate the proportion of SNPs lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 13 publications
0
87
0
Order By: Relevance
“…This is obviously imperfect, as genotype calling algorithms for microarrays tend to be unreliable at SNPs with low minor allele counts, even if Illumina's proprietary SNP genotype-calling software GenCall for the Illumina microarrays has been reported to exhibit low error rates (Shah et al, 2012). However, in our comparison, any errors in the Omni1-Quad genotypes will contribute the same impact to the comparison of the different variant callers.…”
Section: Discussionmentioning
confidence: 86%
“…This is obviously imperfect, as genotype calling algorithms for microarrays tend to be unreliable at SNPs with low minor allele counts, even if Illumina's proprietary SNP genotype-calling software GenCall for the Illumina microarrays has been reported to exhibit low error rates (Shah et al, 2012). However, in our comparison, any errors in the Omni1-Quad genotypes will contribute the same impact to the comparison of the different variant callers.…”
Section: Discussionmentioning
confidence: 86%
“…S2). We also compared our method with optiCall (Shah et al, 2012) and found for 10 705 singletons, the SWC of optiCall was 98.21% versus 99.27% for zCall ( Supplementary Fig. S3).…”
Section: Resultsmentioning
confidence: 99%
“…Clustering of the intensities and genotype calling was performed using the optiCall clustering program, with a no-calling cutoff set to 0.7. 27 To avoid false positive signals in the genome-wide association studies analysis, a stringent quality control (QC) was performed using PLINK software version 1.07. 28 …”
Section: Genetic Analysismentioning
confidence: 99%